Optimization of gadolinium-doped zinc oxide films for diluted magnetic semiconductor and its effects on organic solar cell performance - Che Ani, Noorhidayah (2017)
Diluted Magnetic Semiconductors (DMS) are being actively studied as a major step towards the realization of spintronic devices. However, to obtain the DMS with ferromagnetic behaviour at room temperature is the main obstacle in the fabrication of spintronic devices. This obstacle has prompted significant research efforts aimed at exploring new DMS. In this research, Gadolinium (Gd) was doped with Zinc Oxide (ZnO) to explore the feasibility of making new DMS. The Gd-doped ZnO (Zn1-xGdxO) was synthesized using the sol-gel spin coating technique. Parameters, such as the type of solvent, annealing environment and Gd contents, were varied in order to optimize the structural and magnetic properties. The optimum properties were obtained from a prepared solution using ethanol solvents, annealed in an Ar-environment with 8 % Gd contents. The structural, surface topology, optical, electrical and magnetic properties of the film were studied in detail. Structural studies revealed that the film had a hexagonal wurtzite structure. Surface topologies showed that the film had a smooth and uniform surface. In addition, the film was also highly transparent within visible range with optical transmittance of approximately ~ 90 %. The electrical analysis revealed that the resistivity and carrier concentration was about 3.17 x 10-3  cm and 8.27 x 1014 cm-3, respectively. The magnetic studies showed that the film was ferromagnetic at room temperature with a magnetization of 0.0423 emu/g. The effect of ferromagnetic Gd-doped ZnO film on device performance was demonstrated by fabricating the Spin-Polarized Organic Solar Cell (Spin-OSC). It was found that the ferromagnetic Zn0.92Gd0.08O film contributed immensely to the performance of OSC. The result showed that the efficiency of Spin-OSC (0.16 %) was higher than conventional-OSC (0.04 %). Thus, this proved the possibility of spintronics in optoelectronic applications, especially in solar cells.